Protective Effects of Olive Oil on Liver Tissue in Swiss Rats Treated with Cyclophosphamide: A Histopathological Study. - H. Amer, Abeer; H. Boshahma, Fatma; H. Masoud, Ali; E. Lehmidi, Tareq; A. Elharabi, Thanaa; S. Sassi, Heba; M. Eldresi, Salwa; M. Elfazani, Zahra; H. Alferjani, Nisreen (Benghazi University Medical Journal, 2025)
Background: Cyclophosphamide (CP) is a commonly used chemotherapy agent acknowledged to have hepatotoxic effects. Olive oil, which is high in antioxidants, may offer protective benefits against damage caused by such drugs. Aims: This study aims to search the potential protective effects of olive oil on liver toxicity induced by cyclophosphamide in a rat model. Materials and Methods: A total of nine male albino rats were allocated into three distinct groups: A Control group, a CP group receiving 150 mg/kg, and a CP group receiving both 150 mg/kg of CP and 200 mg/kg of olive oil. The doses were administered on days one, three and five. On day seven, liver tissues were harvested for histopathological evaluation. Results: Histopathological analysis showed that CP treatment resulted in extensive liver damage, especially affecting the portal tracts and central veins. The addition of olive oil appeared to reduce some of the toxic effects detected with CP, mainly in the portal tract and sinusoidal regions. Nonetheless, some degree of liver injury persisted in the group receiving both CP and olive oil. These results imply that olive oil may offer a protective benefit against CP induced liver toxicity in rats. Conclusion: The administration of CP led to significant histopathological alterations in the liver tissues of rats. The concurrent use of olive oil seemed to alleviate some of these detrimental effects, likely attributable to its antioxidant properties. These findings suggest that incorporating olive oil could be beneficial as a protective measure during CP chemotherapy.